INCREASING INTEREST IN LEARNING ARABIC WITH INTERACTIVE AND CONTEXTUAL METHODS - Khairanis, Retisfa; Aldi, Muhammad (As-Sulthan Journal of Education, 2024)
This research aims to increase interest in learning Arabic through the application of interactive and contextual methods that are relevant to the needs of students. High interest in learning is an important factor in the success of learning Arabic, especially in the midst of the challenge of low learning motivation among students. Interactive methods, such as group discussions and educational games, as well as contextual methods that connect the subject matter with daily life situations, are expected to increase students' participation and understanding. The research used a qualitative approach with a classroom action research design. Data was collected through direct observation, interviews with students and teachers, and questionnaires to measure the level of interest in learning before and after the application of this method. The data analysis technique involved the description and interpretation of the results of the action to determine the impact of the method used. The results showed that interactive and contextual methods significantly increased students' interest in learning Arabic. Students became more active in learning, showed more enthusiasm, and were able to apply vocabulary and grammar in relevant contexts. Teachers also noted an increase in students' understanding and skills in using Arabic. The implication of this research confirms that the application of interactive and contextual methods can be an effective solution to increase interest in learning Arabic. The contribution of this research provides guidance for educators to adopt more innovative approaches, so that Arabic language learning is not only academically relevant but also interesting and fun for students.